Faktor-Faktor Yang Berhubungan Dengan Dukungan Suami Dalam Pelaksanaan Kelas Ibu Hamil - Marina, Ni Nyoman; Sari, Nita Evriana; Aryawati, Wayan; Mariza, Ana (MIDWIFERY JOURNAL, 2022)
Background Pregnant women class is a face-to-face group learning activity  which aims to increase knowledge and skills regarding pregnancy, childbirth, pregnancy care, newborn care, myths and diseases. Data from Way Dente Health Center shows that there are only 32.1% pregnant women attending the class . The purpose of this study was to identify the factors concerning the husband's support to the attendance of pregnant women class  in Way Dente Health Center Work Area, Tulang Bawang Regency, Lampung.Methods This research was quantitative with Cross Sectional approach. The population of this study were all husbands of pregnant women with gestational age ≥ 28 weeks as many as 111 people, with the samples were 87 respondents. The object of this research was husband's support in the attendance of pregnant women's classes, knowledge, education, husband's attitude and occupation. The study was carried out at Way Dente Health Center Work Area, Tulang Bawang Regency, Lampung in June - July 2021. Data collection used a questionnaire sheet distributed to respondents. Data analysis was univariate and bivariate (chi square).Result showed that the characteristic of 87 respondents were 50 (57.5%) people categorized with high husband support, 54 (62.1%) people earned junior high school education, 34 (39.1%) people having good knowledge, 45 (51.7%) people having casual work,  45 (51.7%) people showing a positive husband's attitude. There were relationships among education background (p value = 0.013 OR 3.625), husband's knowledge (p value = 0.012), husband's attitude (p value = 0.004, OR = 4.044), and husband's occupation (p value = 0.020 OR 3.125) towards husband's support in attending pregnant women class at Way Dente Health Center working area Tulang Bawang Regency, Lampung.Conclusion There were relationships among education,husband's knowledge, husband's and husband's occupation towards husband's support in attending pregnant women class at Way Dente Health Center working area Tulang Bawang Regency, Lampung.Suggestion to educate husbands about the importance of pregnant women's classes so that the husbands have a positive attitude towards pregnant women's classes. Keywords : Class of pregnant women, husband support, knowledge, husband's attitude, education, and occupation ABSTRAK Latar Belakang Kelas ibu hamil merupakan suatu kegiatan belajar kelompok dalam bentuk tatap muka yang bertujuan untuk meningkatkan pengetahuan dan keterampilan mengenai kehamilan, persalinan, perawatan kehamilan, perawatan bayi baru lahir, mitos dan penyakit. Pada Puskesmas Way Dente yang memanfaatkan kelas ibu hamil sebesar 32,1%. Tujuan penelitian diketahui faktor-faktor yang berhubungan dengan dukungan suami dalam pelaksanaan kelas ibu hamil di Wilayah Kerja  Puskesmas Way Dente Kabupaten Tulang Bawang Lampung.Metode Jenis penelitian kuantitatif dengan pendekatan Cross Sectional. Populasi penelitian ini adalah seluruh suami ibu hamil usia kehamilan ≥ 28 minggu sebanyak 111 orang dengan sampel yang digunakan sebanyak 87 responden. Objek penelitian ini adalah dukungan suami dalam pelaksanaan kelas ibu hamil, pengetahuan, pendidikan, sikap suami dan pekerjaan. Penelitian telah dilaksanakan di Wilayah Kerja Puskesmas Way Dente Kabupaten Tulang Bawang Lampung pada bulan Juni - Juli 2021. Pengumpulan data menggunakan lembar kuesioner yang di berikan kepada responden. Analisi data secara univariat dan bivariat (chi square).Hasil penelitian diketahui bahwa dari 87 responden, pada sebagian responden dengan dukungan suami tinggi sebanyak 50 (57,5%) dengan pendidikan smp sebanyak 54 (62,1%) dengan pengetahuan baik sebanyak 34 (39,1%) responden dengan pekerjaan serabutan sebanyak 45 (51,7%) dengan sikap suami positif sebanyak 45 (51,7%) responden. Ada hubungan pendidikan (p value= 0,013 OR 3,625), pengetahuan suami (p value = 0,012), sikap suami (p value = 0,004, OR = 4,044), dan pekerjaan suami (p value =0,020 OR 3,125) dengan dukungan suami dalam pelaksanaan kelas ibu hamil di wilayah kerja Puskesmas Way Dente  Kabupaten Tulang Bawang Lampung.Kesimpulan  Ada hubungan pendidikan pengetahuan suami (p value = 0,012), sikap suami (p value = 0,004, OR = 4,044), dan pekerjaan suami (p value =0,020 OR 3,125) dengan dukungan suami dalam pelaksanaan kelas ibu hamil di wilayah kerja Puskesmas Way Dente  Kabupaten Tulang Bawang Lampung. Saran diharapkan tenaga kesehatan untuk mengedukasi suami mengenai pentingnya kelas ibu hamil sehingga suami memiliki sikap positif terhadap kelas ibu hamil.   Kata Kunci :    kelas ibu hamil, dukungan suami, pengetahuan, sikap suami, pendidikan, dan pekerjaan